If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4u) = (5) + u (4u) = 5 + u Solving (4u) = 5 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. (4u) + -1u = 5 + u + -1u Combine like terms: (4u) + -1u = 3u 3u = 5 + u + -1u Combine like terms: u + -1u = 0 3u = 5 + 0 3u = 5 Divide each side by '3'. u = 1.666666667 Simplifying u = 1.666666667
| (3d+4)=0 | | 4=2+4x | | 5(1.5-w)=71.25 | | 24=4-2n | | Y=12-3y | | 4x-1=8.5 | | 14=4+5n+5n | | 5x+5=-2 | | -4x+8=-24 | | 5m+18=-5m-24-4m | | 8ln(x+2.8)=12.8 | | 2(x)-3=11 | | -8(h+59)=-96 | | 4x+6=-3 | | 3(q-5)-2=4 | | 0.33ln(5-x)=0 | | (6-y)(6-y)=0 | | 7(5x+6)=18-(1x+6) | | 4(z-18)-20=-20 | | 37.4x=54.8 | | 6x+5x=7 | | 4(0.8x+15)=2(3+1.6x) | | 7x-8-2x=12 | | 4(h+2)+3=15 | | 5wx^2-2wx^2=3 | | 5=3(p+1)-1 | | ln(x-4)xln(x^2)=42 | | 12x+5=14x-21 | | (2q)=9-3q | | (2)q=9-3q | | 2x(2x-1)=3 | | 1-6x+5x=-6 |